Cassava: booming outputs meet flagging markets - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2005)
The economic potential for cassava a crop crucial for food security, especially in Africa remains largely untapped, despite constant growth in output...